Integration of Local Knowledge and Adaptive Practices in Small-Island Water Governance: An Ethnohydrological Study of Negeri Soya, Ambon, Indonesia - Silvia Parera; Bokiraiya Latuamury; Husain Marasabessy (Forest and Nature, 2026)
Water resource sustainability in tropical small-island environments is increasingly challenged by ecological degradation, seasonal variability, and limited infrastructure, particularly in areas where springs serve as the primary freshwater source. In customary forest landscapes, water governance is embedded in local knowledge systems, ritual practices, and community institutions that regulate resource use while supporting ecosystem conservation. This study examines how local knowledge, customary institutions, and adaptive practices contribute to spring conservation and community-based water governance in Negeri Soya, Ambon, Indonesia. Employing a convergent mixed-method approach, the research combines ethnographic techniques—comprising in-depth interviews, participant observation, and visual documentation—with quantitative analysis using the Chi-square test. The findings reveal that water governance is structured through a culturally embedded system in which ritual practices, traditional artifacts, and hierarchical customary institutions collectively regulate access, maintain water quality, and support spring conservation. Quantitative results indicate that customary sanctions and temporary access restrictions are the most influential mechanisms in ensuring compliance under ecological and social pressures, while deliberation and knowledge transmission contribute to long-term system resilience. The study also identifies the role of simple monitoring tools, such as manual flow observation and recording, in strengthening adaptive responses to seasonal variability. Furthermore, artifacts such as Perigi Soya, Tempayan Soya, and communal storage facilities function not only as physical infrastructure but also as socio-ecological interfaces reinforcing governance legitimacy. The results demonstrate that water management in Negeri Soya operates as a multi-layered socio-ecological system integrating ecological signals with socially legitimate decision-making processes. This research contributes to the advancement of ethnohydrology by providing empirical evidence of how culturally embedded practices and low-cost technologies can support sustainable, community-based water governance in vulnerable small-island environments.